2022
DOI: 10.1021/jacs.2c02817
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Coupling of Alkyl Vicinal Bis(boronic Esters) to an Array of Electrophiles

Abstract: A neighboring boronate group in the substrate provides a dramatic rate acceleration in transmetalation to copper and thereby enables organoboronic esters to participate in unprecedented site-selective cross-couplings. This cross-coupling operates under practical experimental conditions and allows for coupling between vicinal bis­(boronic esters) and allyl, alkynyl, and propargyl electrophiles as well as a simple proton. Because the reactive substrates are vicinal bis­(boronic esters), the cross-coupling descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Recent studies in our laboratory revealed that aliphatic 1,2-bis­(boronic esters) ( 1 , Figure b) are remarkably reactive substrates in Suzuki–Miyaura reactions with the presence of an adjacent organoboronate providing >50-fold rate acceleration in Pd-catalyzed cross-coupling . More recent experiments involving copper catalysis revealed similar substrate activation, with the origin of rate enhancement being traced to the intermediacy of a strained cyclic chelated ate complex (i.e., 4 , Figure b) . Indeed, species such as 4 and 5 were detected spectroscopically upon treatment of the vicinal bis­(boronic ester) with methoxide.…”
mentioning
confidence: 99%
“…Recent studies in our laboratory revealed that aliphatic 1,2-bis­(boronic esters) ( 1 , Figure b) are remarkably reactive substrates in Suzuki–Miyaura reactions with the presence of an adjacent organoboronate providing >50-fold rate acceleration in Pd-catalyzed cross-coupling . More recent experiments involving copper catalysis revealed similar substrate activation, with the origin of rate enhancement being traced to the intermediacy of a strained cyclic chelated ate complex (i.e., 4 , Figure b) . Indeed, species such as 4 and 5 were detected spectroscopically upon treatment of the vicinal bis­(boronic ester) with methoxide.…”
mentioning
confidence: 99%
“…36−41 Perhaps most relevant to these observations, Morken and co-workers recently found that vicinal aliphatic bis(boronic esters) undergo relatively rapid transmetalation to Cu(I) and proposed a mechanism involving a key B−O−B-linked cyclic "ate" complex. 42 Pathway A is directly analogous to the one advanced by Stahl and co-workers, who used EPR spectroscopy to support the proposal of an acetate-bridged complex arising from the interaction of boronic acid (or methylboronate) with Cu(OAc) 2 . Pathway B is closely related, with the difference being that it is the substrate-derived boronic ester, rather than free boronic acid that engages with Cu(OAc) 2 to generate the acetate-bridged species.…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…Two detailed proposals are shown in Scheme , both involving a pre-transmetalation complex similar to that proposed by Stahl and co-workers (see intermediate I , Scheme b) while also accounting for the accelerating effect of the “spectator” boronic ester group, which engages the incoming boronic acid reagent through the formation of a B–O–B linkage . Related binuclear B–X–B complexes have been implicated in other organoboron-mediated and catalyzed transformations. Perhaps most relevant to these observations, Morken and co-workers recently found that vicinal aliphatic bis­(boronic esters) undergo relatively rapid transmetalation to Cu­(I) and proposed a mechanism involving a key B–O–B-linked cyclic “ate” complex . Pathway A is directly analogous to the one advanced by Stahl and co-workers, who used EPR spectroscopy to support the proposal of an acetate-bridged complex arising from the interaction of boronic acid (or methylboronate) with Cu­(OAc) 2 .…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, we found that 1,1-disubstituted alkenes readily undergo addition reactions to give the difunctionalization products bearing quaternary carbon centers in good yields (14-26, 65%-94%), including three examples with highly crowded triaryl quaternary carbon centers (24)(25)(26). These results clearly illustrate the unique features of this method compared to transition-metal-catalyzed difunctionalizations [36][37][38][39] , in which the formation of the quaternary carbon center remains a great challenge [40][41][42] . Surprisingly, a series of substituents, such as boronic After establishing that a wide array of aromatic alkenes is applicable to this transformation, we turned our attention to the scope of electrophiles with different types of leaving groups.…”
Section: Synthetic Scopementioning
confidence: 81%